The elephant in the room - Sloan, Holly Goldberg, 1958- (Dial Books for Young Readers, 2022)
Missing her mother who has returned to Turkey to resolve an immigration problem, sixth-grader Sila welcomes a very large distraction in her life when she helps a surprising new friend rescue a circus elephant.